Bahasa Inggris - Yona Bayu Prasetyo; Saddan Pramana Putra; Agung Dwi Darmawan; Hadiono Hadiono; Vega Mareta Sceisarriya; Achmad Furqon Bildhonny; Andryas Yuniarto (Universitas Hamzanwadi, 2026)
Caffeine is a widely used ergogenic aid known to enhance both physical and cognitive performance. Its potential to influence lactate accumulation during high-intensity exercise, such as sprinting, remains an area of interest.This study aimed to investigate the effect of 100% Arabica caffeine consumption on blood lactate levels following sprint activity.Using a pretest-posttest control group design, 32 sprint athletes from KONI Madiun (divided into treatment and control groups) participated in a 30-meter sprint test repeated three times. The treatment group consumed 3–6 mg/kg body weight of caffeine in the form of an Americano one hour prior to testing. Blood lactate levels were measured post-sprint using a lactate analyzer. Independent t-tests were conducted with a significance level of p < 0.05. The treatment group consistently exhibited lower lactate levels compared to the control group across all sprint stages. Statistically significant differences were observed in Sprint 1, Sprint 2, and the total lactate accumulation while Sprint 3 showed no significant difference (p = 0.072). The findings suggest that caffeine consumption before sprinting may reduce lactate accumulation and improve metabolic efficiency. Caffeine intake in the form of 100% Arabica Americano has a significant effect in lowering blood lactate levels during repeated high-intensity sprint efforts. This supports its potential use as an ergogenic aid in anaerobic sports. However, variability in individual response highlights the need for tailored supplementation strategies and further investigation into long-term physiological adaptations.